2009
DOI: 10.1038/sj.bjc.6604954
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer variability in mammography screening and effect of type and number of readers on screening outcome

Abstract: We prospectively determined the variability in radiologists' interpretation of screening mammograms and assessed the influence of type and number of readers on screening outcome. Twenty-one screening mammography radiographers and eight screening radiologists participated. A total of 106 093 screening mammograms were double-read by two radiographers and, in turn, by two radiologists. Initially, radiologists were blinded to the referral opinion of the radiographers. A woman was referred if she was considered pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 31 publications
3
43
1
3
Order By: Relevance
“…In France, organized mammography screening is a free service offered biannually to asymptomatic women aged 50-74 years old and consists of a clinical examination and a two-view mammography. By associating clinical breast examinations with the double reading of normal mammograms by a second radiologist, organized mammography screening (OrgMS) programmes ensure a higher rate of cancer detection at an earlier stage [2][3][4][5][6][7]. In many developed countries, OrgMS programmes coexist with opportunistic mammography screening (OppMS).…”
Section: Introductionmentioning
confidence: 99%
“…In France, organized mammography screening is a free service offered biannually to asymptomatic women aged 50-74 years old and consists of a clinical examination and a two-view mammography. By associating clinical breast examinations with the double reading of normal mammograms by a second radiologist, organized mammography screening (OrgMS) programmes ensure a higher rate of cancer detection at an earlier stage [2][3][4][5][6][7]. In many developed countries, OrgMS programmes coexist with opportunistic mammography screening (OppMS).…”
Section: Introductionmentioning
confidence: 99%
“…Although screening mammography is currently the best way to detect early breast cancer, there continues to be unexplained variability in radiologists’ interpretive performance [13]. To better understand this variability, studies examining radiologist characteristics associated with clinical accuracy have focused on interpretive volume [46], years of experience [5, 7], fellowship training [2, 7], radiologists’ enjoyment of interpreting mammograms [8], the balance of screening and diagnostic interpretations [4], and the influence of medical malpractice [9].…”
mentioning
confidence: 99%
“…In a multicenter study, Taplin et al [20] reported a PPV1 of 4.1% and PPV2 of 38.8%. Duijm et al [21] observed a PPV2 of 37.4%. Rosenberg et al [22] observed a PPV1 of 4.8% and a PPV2 of 24.6%.…”
Section: Discussionmentioning
confidence: 94%